PENGARUH KOMPETENSI, INDEPENDENSI DAN OBJEKTIVITAS TERHADAP KUALITAS AUDIT DENGAN ETIKA AUDITOR SEBAGAI VARIABEL MODERASI (Studi Pada Kantor Akuntan Publik di Jawa Tengah dan DIY) - Agnes Cahyani, 14.05.52.0077; Himmawan, Arief (Students' Journal of Accounting and Banking, 2018)
Audit quality is the quality of the work of an auditor who is shown with a reliable report of the results of the examination. Audit quality is influenced by various factors such as independence, experience, objectivity, competence and auditor ethics. This study aims to examine the influence of competence, independence, objectivity on audit quality with auditor ethics as a moderation variable. The population in this study are all auditors who work in Public Accounting Firm in Jawa Tengah and Daerah Istimewa Yogyakarta (DIY). Sampling was done by using purposive sampling method and obtained a sample of 65 respondents. The method of collecting primary data was conducted through survey method using questionnaire. The data obtained were analyzed using multiple linear regression model and absolute differenc test to test the effect of moderation variable by SPSS 19.0. The results of this study show that competence, independence, objectivity have a positive effect on audit quality. The ethics of the auditor does not moderate the influence of competence, independence, on audit quality. And the ethics of the auditor does moderate the influence of objectivity on audit qualit. Keywords: competence, independence, objectivity, auditor ethics and audit qualit.